Indonesian Muslim Students' Perception on the Concept of Peace, Characteristics of Peaceful People, and Non-Peaceful Experiences in Madrasah Aliyah - Saripudin, Mohamad; Hamdan, Amirul Hazmi; Asiah, Nur (UIII Press, 2023)
Peace education holds a crucial position within UNESCO’s four pillars of education. Promoting peace was identified as primary focus in the Sustainable Development Goals (SGD). Peace serves as the ultimate objective of education, the agenda set forth by the Sustainable Development Goals (SGD), and is the core principal taught by religious teachings. Despite its significance, achieving complete peace remains elusive within the realms of schools, communities, and world at large. To date, no study has been conducted to investigate the understanding of peace among Muslim students in Indonesia. Therefore, this study aims to explore the concept of peace, the characteristics of peaceful people, and non-peaceful experiences in schools encountered by students. This study employed a qualitative research approach, utilizing phenomenological method. A total of 28 students, (13 males and 15 females) were selected from Madrasah Aliyah as participants of this study. The data in this study was collected through structured interviews and analyzed qualitatively, using Interpretative Phenomenological Analysis (IPA). The findings of this study revealed that students' understanding of peace included elements of self-acceptance, maintaining harmonious relationships with others, and experiencing tranquility. Muslim students acknowledge that maintaining peace requires the individuals to practice the art of patience and composure, self-acceptance and understanding, and the ability to control their emotions. Non-peaceful experiences emerged as a result of various factors, such as favouritism and punitive actions towards students by teachers, including conflicts among students, and as well as instances of bullying, racism, and exclusion. According to the findings, it is evident that there is a need for further improvement in implementing a peaceful environment within schools. Teachers play a vital role in fostering the culture of peace in the classrooms. They can achieve this by creating a welcoming and inclusive environment for students, encouraging their active participation, and facilitating social engagement among students from diverse backgrounds to promote a peaceful school environment.